Integrating age old cultural reproductive health practices with modern medicine to bring down morbidity and mortality among Birhor tribes of Jharkhand, India - Kaur, Tejinder Pal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Among the primitive tribe of Jharkhand, Birhor’s are the smallest group, and have been tagged as 'critically endangered' with population ~5000 (Census 2011). Traditional health care practices, traditional medicines, rituals and supernatural methods of treatment are integral part of tribal community. The main objective of the study was to integrate the cultural health practices focusing on reproductive health with modern medicine so that it impacts maternal and infant mortality. Methods: A three- and half-year study was done in one of the outreach clinical area of Tata Steel Rural development society in Chotabanki village, East Singhbhum, Jharkand, India, among the Birhor tribes. The study was based on primary quantitative data -Data collection was by interviewing the respondents using questionnaires. Numerous interactive sessions with community members were conducted to learn about their cultural practices related to maternal and infant health. Results: There was a definite change in behaviour in some of traditional health practices, related to maternal and child health. Acceptance of modern health services impacted the health indicators, resulting in increase in population growth by 7.6% with zero still birth, maternal and infant mortality. Conclusions: As medical professionals, extra effort should be taken to understand their cultures regarding health. By establishing a balance between their age-old cultural practices and modern medicine, we may get healthier and résistance free community & success in controlling morbidity and mortality.